Tingkat kecemasan dan pengaruhnya terhadap hasil belajar siswa pada pelajaran matematika - Nurhayati Sri Utami; Nyiayu Fahriza Fuadiah (Math Didactic: Jurnal Pendidikan Matematika, 2018)
This study aims to determine how the level of anxiety experienced by students and their influence on learning outcomes in mathematics learning. Background by the emergence of anxiety experienced by students in mathematics lessons that affect student learning outcomes. This research uses quantitative research using the One-Shot Case Study method. The subjects of this study were 30 students of class VIII of SMP 40 Palembang consisting of 14 men and 16 women. The data used is secondary data in the form of student anxiety data and learning outcomes data in mathematics learning. Data analysis in this study using the Kolmogorov-Smirnov One-Sample normality test while to see the effect of anxiety experienced by students was done by correlational non-parametric statistical test with the Spearman Rank test. Tests are carried out using IBM SPSS 24 application. The results of this determination show that the majority of mathematics anxiety in Palembang's 40th Junior High School students is included in the medium category with a percentage of 57% and the influence of anxiety on student learning outcomes in mathematics learning is not significant, but the higher student anxiety scores then the lower the learning outcomes.